Roll control reversal of variable swept wing in supersonic flow - Ibren, Mohamed; Sulaeman, Erwin; Legowo, Ari; Abdullah, Nur Azam (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Roll control reversal of a variable swept wing is investigated in the present paper. The wing model is based on the Rodden-Love forward swept wing which is modified in the present work so that it can swept forward and backward. The flexural and torsional wing flexibilities are considered in the analysis so that their influence on the aileron control effectiveness can be assessed. The influence of the vertical tail is included in the trim analysis in several flight altitudes. A parametric study by varying the wing bending and torsional stiffness is conducted. The result shows that the aileron control effectiveness of the forward swept wing performs better than the backward swept wing for the present model.